(untitled) (International Journal of Social Research & Innovation, 2018)
Modernisation and urbanisation has come at a cost to Maldivian children, making them more vulnerable to social ills and psychological diseases. Life Skills Education (LSE) has been integrated into the 2014 Maldives National Curriculum as a way to avert the emotional and psychological crises of children growing up in a rapidly changing society. Rather than questioning how this new initiative is introduced within the curriculum and the possible outcomes of the initiative, this paper aims to explore how knowledgeable and prepared the teachers believe they are to teach Life Skills to children. A cross sectional survey was completed by 186 teachers of two schools of Male’, Maldives. Life Skills Education has been taught in some form in both schools since 2004. Four factors linked to teacher preparedness were analysed, namely: (1) teachers’ attitude to LSE; (2) teachers’ motivation to implement LSE; (3) teachers’ perceived professional mastery; and (4) participation in ongoing professional development, all of which have direct impact on successful implementation of Life Skills Education. All four factors have strong correlation to successful implementation of Life Skills Education. Only 13% of the teachers in this study indicated that they believed they had the capacity to deliver Life Skills Education in the curriculum fully. This study identified the urgent need for LSE to be incorporated into initial teacher training and for policy makers and school leaders to ensure that teachers have ongoing effective support to develop life skills of vulnerable children who live in challenging home environments.